Optimization of community-based breeding programs - Getachew, Tesfaye; Rekik, Mourad; Rischkowsky, Barbara; Belay, Berhanu; Goshmie, Shenkutie; Ambecho, Zelalem Abate; Giorgis, Kebede H.; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2022)
Any breeding program undergoes numerous stages of improvement and adjustment and is never completely flawless from the beginning. Initial selection in the community-based breeding programs (CBBPs) were made only based on phenotypic performance, disregarding the relationships between individuals. Following the accumulation of pedigree and performance data, the BLUP animal model has now been employed. Significant genetic gain for selection qualities were achieved in Ethiopian sheep CBBPs. However, there are still ways to maximize genetic advancement and overall advantages of the breeding programs. A method to maximize the current CBBPs was studied, which included increasing selection intensity and sire use strategy, index-based selection, enhancing breeding females' reproductive productivity, and connecting CBBPs with the production unit. The researchers attended planning and training sessions regarding CBBP optimization. The researchers later returned to their respective villages and implemented CBBP optimization as appropriate.